Animatrix - Chung, Peter; Davis, Don, 1957-; Wachowski, Andy; Wachowski, Larry (Warner Bros, 2003)
The Animatrix is a collection of several animated short films, detailing the backstory of the "Matrix" universe, and the original war between man and machines which led to the creation of the Matrix.